Building Independence Through Self-Prompting with Technology - Reinecke, Dana R. (Journal of the American Academy of Special Education Professionals, 2019)
Self-management is an effective, well-researched set of strategies for increasing, decreasing, and maintaining one’s own behavior. Self-management strategies have been shown to be effective in supporting students with disabilities, with the ultimate outcome of greater independence. Self-prompting, an important step in self-management, has become even easier to learn and implement with currently-available technology. This paper discusses the benefits of self-prompting and how technology may be used to teach and improve self-prompting repertoires, and offers several suggestions for applications to facilitate self-prompting.